Palinologia de Agavaceae, una contribucion biosistematica - Ojeda Revah, L.=700 1 Ludlow Wiechers, B.
(En, Es)
ilus., 66 ref.
Keywords: AGAVACEAE; CARIOTIPOS; PALINOLOGIA; BIOGEOGRAFIA; ANATOMIA DE LA PLANTA; POLEN; TAXONOMIA; MEXICO